A Inorganic Waste Management as a Medium for Environmental Education and Student Creativity Development - Sunardi; Jumiati Ilham; Didiet Haryadi Hakim; Sitti Suhada; Wildan; Hasmah (Sakura Digital Nusantara, 2026)
The problem of inorganic waste in school environments requires an educational approach that not only emphasizes knowledge but also provides practical experiences that foster students’ creativity and environmental awareness. This community service program aimed to strengthen students’ understanding of inorganic waste management and provide direct experience in transforming used materials into useful creative products. The activity was conducted at SD Negeri 1 Suwawa Selatan, Bone Bolango Regency, involving 30 fourth- and fifth-grade students. The implementation method consisted of preparation, interactive socialization, demonstration, group-based recycling practice, and descriptive evaluation through participation observation, product assessment rubrics, field notes, and documentation. The results showed positive achievements in four main aspects: students’ active involvement in discussions and practice, their ability to identify organic and inorganic waste, their initial understanding of the 3R principles (reduce, reuse, recycle), and their ability to produce simple recycled products such as flower pots, pencil holders, and photo frames from used materials. The activity also promoted teamwork, responsibility in completing products, and awareness of maintaining school cleanliness. Therefore, inorganic waste management can be used as a concrete, low-cost, applicable, and easily replicable medium for environmental education to support character education and the development of elementary school students’ creativity.